Here's the question you clicked on:
babydoll332
Perform the requested operation or operations. f(x) = 4x + 7, g(x) = 3x^2 Find (f + g)(x).
Almost. You lost the "f(x) = " and you probably shoudl re-arrange to standard form.
would it be 12x^3 +21x
wait sorry no 4x+7-3x^2
No. You must learn to recognize "like" terms. x + x = 2x 2x^2 + x^2 = 3x^2 3x^2 - x cannot be simplified. The total of all variable exponents is an important part of "like" term.
I'm pretty puzzled by this. You had it right in the first place. Why did you try four other things after that? Why would it lead to division?! I suggested ONLY that you work on your notation.